2004
DOI: 10.1016/j.physa.2004.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Poincaré recurrences and multifractal properties of genomic sequences

Abstract: We propose the return times spectra as a tool to analyze the genomic sequences. The spectra discriminate between regular, chaotic and mixed dynamical systems since generally their decay follows respectively an exponential law, a power law or is a linear combination of them. The analysis of words of n bases from a DNA sequence exhibits the same exponential behavior for the coding and noncoding component. The multifractal analysis shows a definite difference, which suggests a less uniform structure for the nonco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Surprisingly, this powerful tool of dynamical systems has not been applied for detailed statistical studies of the DNA sequence, which also can be viewed as a symbolic trajectory. There have been only a few earlier attempts going in this direction including researchers in dynamical systems [11] and bioinformatics [12][13][14]. However, in [11] only short recurrence times with t 4 have been considered and it was concluded that the probability of recurrences decays exponentially.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, this powerful tool of dynamical systems has not been applied for detailed statistical studies of the DNA sequence, which also can be viewed as a symbolic trajectory. There have been only a few earlier attempts going in this direction including researchers in dynamical systems [11] and bioinformatics [12][13][14]. However, in [11] only short recurrence times with t 4 have been considered and it was concluded that the probability of recurrences decays exponentially.…”
mentioning
confidence: 99%
“…The comparison with random data sequences and the known results for dynamical maps [5][6][7][8][9][10] allowed us to establish new, interesting features for the Poincaré recurrences of the DNA sequence. Our approach allowed to analyze the recurrences with time t being by five to six orders of magnitude larger than those reached in [11][12][13][14]. For the Homo sapiens (HS) database we performed statistical analysis for 1.5 × 10 10 base pairs (bp).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multifractal studies have been undertaken in other domains such as DNA sequences [18], turbulence [5], day and night heart rate characteristics [17], alterations with disease and aging [7]. In this study, we have confined our scope to extract only the multifractality present in the pulse waveforms.…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
“…Thereafter, much effort has been devoted to the analysis of symbolic trajectories in very different contexts: stochastic processes [21], biological data [22] and literary texts [23], to mention just a few. These tools have been applied to genomics in different forms for about the last 10 years [24,25], becoming nowadays rather common, e.g. for the reconstruction of the phylogenetic tree [18,19], for the detection of CpG islands [26] and for the characterization of long-range correlations in DNA [27].…”
Section: Introductionmentioning
confidence: 99%